Combination of a floating clavicle and a posterior shoulder dislocation: An “Unhappy Triad” of the shoulder girdle - Schliemann, Benedikt (Medknow Publications & Media Pvt Ltd, 2014)
We present a case of a 31-year-old man who suffered from a floating clavicle in combination with a reverse Hill-Sachs lesion of his right shoulder girdle after a bicycle accident. Operative treatment was performed using minimal-invasive and arthroscopically assisted techniques. We strongly recommend an early CT scan with later 3-dimensional reconstruction to detect and fully understand these complex injuries.